The psychological dynamics of the combat sports experience: how the phenomenological specificity of corporal fighting prevents violence and promotes the development of the practitioner - Barreira, Cristiano Roque Antunes; Telles, Thabata Castelo Branco; Gutiérrez-García, Carlos; Andrieu, Bernard (Frontiers in Psychology, 2025)
Psychological research on martial arts and combat sports (MA&CS) often neglects the essential specificity of the lived experience of combat, resulting in a lack of a unified conceptual framework. This article proposes a phenomenological perspective to clarify the unique psychological dynamics and developmental potential inherent in corporal fighting. Applying classical phenomenology, and drawing upon empirical-phenomenological research based on interviews across nine MA&CS modalities, we analyze the constitutive structures of this lived experience. We identify corporal fighting as a reciprocal, embodied struggle and foundational, distinct from brawl or play-fighting. Five essential forms (corporal fighting, duel, self-defense, instrumental offensive combat, play-fighting) are distinguished by intentional structures. Traditional, modern, and military martial arts simulate duel, self-defense, and instrumental aggression; combat sports directly express corporal fighting. The lived experience of combat is oscillatory, dynamically shifting between forms based on affective, empathic, and motivational modulations. Training fosters development by mediating these transitions, cultivating reflection and resilience. Maintaining this structure requires empathic vigilance, affective modulation, and a sensible norm. Understanding this phenomenological specificity grounds the proposition of a Psychology of MA&CS, clarifying how combat promotes ethical development and intersubjective formation by sustaining experiential tension.